Stability of seed yield and its component traits in fennel (Foeniculum vulgare) - VERMA, PREETI; SOLANKI, R K (The Indian Journal of Agricultural Sciences, 2015)
Stability of eleven genotypes of fennel (Foeniculum vulgare M) was assessed for yield and component traits based on three years consecutive experimentation, i.e. 2009-2011. Mean square due to environment + (variety × environment) was significant for all the traits except number of umbellets per umbel indicating the existence of genotype × environment interaction. Based on the mean performance, regression coefficient and deviation from regression values, it was found that the stability of yield is imparted in the genotypes, viz. UF 281, AF 1, GF 11, JF 586 2/5, HF 131 and NDF 16 through the stable performance of major yield contributing traits like primary and secondary branches, number of umbels and umbellets, number of seeds/plant and test weight. These genotypes may be useful genetic resources for development of high yielding, stable varieties in fennel.